TECHNOLOGIES FOR IMPROVING THE QUALITY OF TEACHING FOREIGN LANGUAGES TO CADETS OF THE HIGHER MILITARY EDUCATIONAL ESTABLISHMENTS - Saodat Zafarovna Mirpayazova (Journal Park Publishing, 2023)
The article describes the potential of the educational establishment, its opportunities in educational activities to ensure quality education, that is, the necessary conditions for obtaining comprehensive education, the possibilities of creating an educational environment, material base, and the system of ensuring the quality of education that meets the requirements of the society in a modern educational establishment. This, in turn, is said to include a set of tools that guarantee the achievement of educational outcomes in accordance with society's established norms and standards.
Keywords: quality of education, higher military educational establishments, future officers, academic progress, monitoring, foreign language, assessment, competence, individual educational development results, military-professional qualifications.